Promoting Learning through Competition and Improving Quality through Evaluation: The Innovative Model and Promotion Path of Regional Study Tour Brand Construction Driven by "Hundred Routes and Hundred Courses" ——Based on the Practical Exploration in Heilongjiang Province - Liwu Sun; Bin Yu (Education Research on Study Tours and Practice, 2026)
The transformation of study tours from "activity-oriented" to "curriculum-oriented" and from "decentralized" to "branded" is the key to realizing their human-oriented essence. Taking the nationally initiated "Hundred Routes and Hundred Courses Study Tour Premium Curriculum and Route Design Review Activity" in Heilongjiang Province as the research object, this paper reveals its core value as a "catalyst" and "testing ground" for regional study tour brands through whole-process review and data verification. Focusing on ten characteristic themes, the activity has established a scientific process of "city-wide mobilization - multi-dimensional review - open sharing - dynamic iteration". The study finds that "Hundred Routes and Hundred Courses" has successfully built an innovative ecosystem of multi-party collaboration among government, research institutions, schools, enterprises and communities through the competition mechanism, with the core of replacing administrative instructions with open competitions, reshaping the educational core with teaching and research standards, and ensuring public trust and transparency with digital review. Review data shows that the activity has nurtured 105 premium courses, with a 92% correlation between courses and subject standards and a over 95% satisfaction rate among teachers and students. This model not only interprets the brand value of "teaching and research leading, standard first" for study tours in Heilongjiang, but also provides a replicable paradigm from "concept" to "practice" for national study tour practice education.